Effect of Processing Conditions on Flexural Strength Properties of Chicken Feather Fibre (CFF) and Its Hybrid Composites with Polypropylene Resin. Issue 7 (2nd July 2020) - Saravanan, K.; Prakash, C.
ABSTRACT: This study discusses the effect of molding temperature, pressure and time on the final compression-molded hybrid composites with polypropylene resin for its flexural strength. The results of tests conducted to characterize the hybrid composites developed with different proportion of fibers and processing conditions are discussed in this study. When comparing the overall results on the flexural strength of the composites, 25:75 Chicken Feather Fiber (CFF)/Jute composite showed highest flexural strength by keeping minimum temperature, maximum pressure and medium time. The influence of pressure on flexural strength is significant compared to temperature and time. As time increases the flexural strength decreases.